Trading Volume Reaction to the Earnings Reconciliation from IAS to U. S. GAAP* - Chen, Lucy Huajing; Sami, Heibatollah (Contemporary Accounting Research, 2008)
for providing analyst forecast data, available through the Institutional Brokers' Estimate System.These data have been provided as part of a broad academic program to encourage earnings expectation research.We also thank those companies, and the Securities and Exchange Commission, which generously provided copies of Form 20-Fs and Form 20-F filing dates for our research project.'cancelled out' in the averaging process that determines equilibrium prices" (Bamber and Cheon 1995, 418;Kim and Verrecchia 1991).Consequently, when investigating information content, price reaction and trading volume reaction may not yield identical results even for the same event (Bamber and Cheon 1995).Moreover,